Accessibility of Cultural Heritage in the Virtual Environment of Latvia Memory Institutions - Krūmiņa, Līga (Bibliotheca Lituana, 2014)
The aim of research is to evaluate the level of e-service provision in digital collections created by memory institutions (libraries and archives) of Latvia. The problem under study is as follows: digital collections have insufficient usability due to lack of appropriate e-services. The empirical basis for research is e-services of digital collections created by national and regional level libraries, as well as the National Archives of Latvia. The evaluation of e-services is based on 14 indicators within 7 categories: visibility, search, reference, personalization, user participation, instructions, and document delivery. The analysis reveals that the level of eservice development is quite low (only satisfactory): e-services have low visibility, three indicators in personalization category are represented incompletely, and the category of user participation has the lowest rate.